Islamic Underground Movement: Islamist Music in the Indonesian Popular Music Scene - Hidayatullah, Rahmat (Center for Study of Islam and Society (PPIM) Syarif Hidayatullah State Islamic University, 2024)
Since the fall of the New Order regime in 1998, music has become a site of religio-political resistance among the new Islamist generation in Indonesia. This research examines the emergence of Islamist music on the Indonesian underground music scene to show the deepening influence of the Islamist movement among urban Muslim youth and the shifting strategy of the new Islamist generation from structural politics to cultural politics. The emergence of Islamist music indicates how a new generation of Islamists negotiates an Islamist worldview with contemporary popular culture. By maintaining the aggressive character of underground music, they adopt the Western popular culture as a code of resistance against the secular cultural hegemony. They also use popular music as a cultural approach or a strategy to promote the Islamist ideology to all urban Muslim youth.